(untitled) - Kozan, Sakakibara (Tokyo, Japan, 1963)
Contents: This is a book on helmets and armour of the 16th century published in EDO (Tokyo) in 1800, two years after the death of the author
Keywords: Vũ khí và áo giáp, Nhật Bản.,Arms and armor, Japanese.,Mũ bảo hiểm,Helmets